Climate change may affect the future of extractivism in the Brazilian Amazon. (May 2021) - Evangelista-Vale, Jôine Cariele; Weihs, Marla; José-Silva, Leandro; Arruda, Rafael; Sander, Nilo Leal; Gomides, Samuel C.; Machado, Talita M.; Pires-Oliveira, João Carlos; Barros-Rosa, Lucas; Castuera-Oliveira, Luciene; Matias, Renan Augusto Miranda; Martins-Oliveira, Angele Tatiane; et al.
Abstract: The Amazon forest is vulnerable to climate change and anthropic actions, such as fire and deforestation, which together represent a troubling scenario. Many traditional populations that inhabit the region depend on non-timber forest resources for food or economic sustenance. We demonstrated that climate change predicted for 2050 may affect the geographic distribution of 18 species of palms and trees that are extracted and used as resources by traditional populations living in extractive reserves (RESEX). According to our ecological niche models, 11 species may have a reduction in their areas of environmental suitability (AES), and nine of them may disappear from some RESEXs. In addition, 21 RESEXs may lose one or more species, while four may lose all their extractive species. We warn that the lack of socio-environmental diagnoses of these reserves makes it difficult to forecast social impacts and to develop mitigation measures. Finally, we identify priority places for the implementation of conservation policies for extractive species. Highlights: Climate changes may affect extractive species in the Brazilian Amazon. The Extractive Reserves (RESEXs) populations subsistence will be compromised. The mechanisms for biodiversity conservation in the Amazon will be affected. Mitigating measures must be adopted to ensure the future of RESEXs.